Application of Highly Purified Electrolyzed Chlorine Dioxide for Tilapia Fillet Disinfection - Chen-Hsing Yu; Tzou-Chi Huang; Chao-Chin Chung; Hao-Hsun Huang; Ho-Hsien Chen (The Scientific World Journal)
This research aimed to develop an electrolysis method to generate high-concentration chlorine dioxide (ClO2) for tilapia fillet disinfection. The designed generator produced up to 3500 ppm of ClO2 at up to 99% purity. Tilapia fillets were soaked in a 400 ppm ClO2 solution for 5, 10, and 25 min. Results show that total plate counts of tilapia, respectively, decreased by 5.72 to 3.23, 2.10, and 1.09 log CFU/g. In addition, a 200 ppm ClO2 solution eliminated coliform bacteria and Escherichia coli in 5 min with shaking treatment. Furthermore, ClO2 and trihalomethanes (THMs) residuals on tilapia fillets were analyzed by GC/MS and were nondetectable (GC-MS detection limit was 0.12 ppb). The results conform to Taiwan’s environmental protection regulations and act governing food sanitation.